Seed setting and filling under pollination with stored pollen in sunflower (Helianthus annuus L): Seed setting and filling under pollination with stored pollen in sunflower (Helianthus annuus L) - S N SUDHAKARA BABU; M LEELAVATHI; G BALAKISHAN; N PRABHAKAR RAO; A VISHNUVARDHAN REDDY (Journal of Oilseeds Research, 2020)
The challenge of weather and soil variation in block method of planting male and female parents differ, often resulting in delay of flowering up to 3 to 5 days affecting pollination. Four pollen storage periods (3, 4, 5 and 6 days) was compared for seed setting and filling in female parent. The study revealed the potential of stored pollen at 4°C up to 5 days with about 80% seed setting in DRSH-1 hybrid.